Fiscal Policy, Institutional Quality and Economic Growth: Some Evidence from Pakistan (Journal of Social Sciences Review, 2022)
The purpose of this research is to look at the link between fiscal policy, institutional quality, and economic growth in Pakistan. The research employs time series data spanning twenty-five years, from 1996 to 2020. The ADF unit root test is used to verify variable stationarity, the Engle Granger technique is used for cointegration dynamics, and the Error Correction model is used for short term relationships. Overall, the findings demonstrate that both productive and wasteful government spending have a favorable influence on economic growth in the short and long run. In the short and long run, institutional quality has a favorable influence on economic growth. While inflation has a short-term favorable influence on economic growth, but it has a long-term negative impact. The findings suggest that the government should distinguish between productive and unproductive spending and increase investment on productive businesses. The government should place a greater emphasis on improving institutions in order to achieve long-term economic growth.
Keywords: Fiscal Policy; Institutional Quality; GDP; Engle Granger; Error Correction Model